Does N-acetylcysteine improve behaviour in children with autism?: A mixed-methods analysis of the effects of N-acetylcysteine. Issue 4 (2nd October 2019) - Dean, Olivia M.; Gray, Kylie; Dodd, Seetal; Villagonzalo, Kristi-Ann; Brown, Ellie; Tonge, Bruce; Berk, Michael; Byrne, Linda K.
ABSTRACT: Background: Traditional treatment for the behavioural symptoms in autism spectrum disorder (ASD) remains unsatisfactory. There is an urgent need for new, biologically relevant therapies that target both the core and comorbid symptoms that children may experience. This article builds on research previously published by the authors. Method: We report a mixed-methods analysis from a 24-week double-blind randomised controlled trial of adjunctive N -acetylcysteine (NAC) for the treatment of behavioural symptoms in ASD. Ninety-eight children between the ages of 3 and 9 years, diagnosed with ASD, participated in the study. Outcome measures included parents' assessment reports (obtained before, during, and after the trial), clinicians' observations, and the researchers' detailed case notes. Thematic analysis of textual data ( n = 85) was carried out, followed by an evaluation of differences in the frequency with which changes in behaviour were qualitatively reported. Results: Compared with placebo, the parents of the group that received NAC reported improved calmness, decreased aggression and agitation, and greater improvements in verbal communication. Conclusions: These results support the usefulness of NAC for treating potentially disruptive behaviour (e.g., aggression and hyperactivity) in children with ASD and provide a novel finding: potentially improved verbal communication following NAC treatment. This paper supports the utility of a mixed-methods analysis for detecting latent signals in clinical trials.